Multiple CRF01_AE/CRF07_BC Recombinants Enhanced the HIV-1 Epidemic Complexity Among MSM in Shenyang City, Northeast China - He, Shan; Song, Wei; Guo, Gang; Li, Qiang; An, Minghui; Zhao, Bin; Gao, Yang; Tian, Wen; Wang, Lin; Shang, Hong; Han, Xiaoxu (Frontiers in Microbiology, 2022)
The transmission of Unique Recombinant Forms (URFs) has complicated the molecular epidemic of HIV-1. This increasing genetic diversity has implications for prevention surveillance, diagnosis, and vaccine design. In this study, we characterized the HIV-1 URFs from 135 newly diagnosed HIV-1 infected cases between 2016 and 2020 in Shenyang, northeast China and analyzed the evolutionary relationship of them by phylogenetic and recombination approaches. Among 135 URFs, we found that the CRF01_AE/CRF07_BC recombinants were the most common (81.5%, 110/135), followed by CRF01_AE/B (11.9%, 16/135), B/C (3.7%, 5/135), and others (3.0%, 4/135). 94.8% (128/135) of patients infected by URFs were through homosexual contact. Among 110 URFs_0107, 60 (54.5%) formed 11 subclusters (branch support value = 1) and shared the consistent recombination structure, respectively. Four subclusters have caused small-scale spread among different high-risk populations. Although the recombination structures of URFs_0107 are various, the hotspots of recombinants gathered between position 2,508 and 2,627 (relative to the HXB2 position). Moreover, the CRF07_BC and CRF01AE fragments of URFs_0107 were mainly derived from the MSM population. In brief, our results reveal the complex recombinant modes and the high transmission risk of URFs_0107, which calls for more attention on the new URFs_0107 monitoring and strict control in the areas led by homosexual transmission route.